Behavior of Strengthened Glass under High-Velocity Impact - Vlasov, A.S.; Zilberbrand, E.L.; Kozhushko, A.A.; Kozachuk, A.I.; Sinani, A.B. (Проблемы прочности, 2002)
The aim of this work was to compare the behavior of untreated glass and glass treated by hydrofluoric acid, as well as to determine factors controlling high ballistic characteristics of the strengthened glass.